ANALISIS BEBAN KERJA MENTAL, FISIK SERTA STRES KERJA PADA PERAWAT SECARA ERGONOMI DI RSUD Dr. ACHMAD MOCHTAR BUKITTINGGI - Srie Wulandari; Samsir '; Rio J M Marpaung (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the level of mental and physical workload and work stress to the nurses in Dr. AchmadMochtar Hospital in Bukittinggi. This research is a descriptive study, which the research looking for a variable value without connect it with other variables. The file in this study conducted by questionnaire. The result of the descriptive analysis of physical workload indicates the light category which is 100-200 kcal/hour. For the mental workload is average at 67,51 for ICU/ICCU, 76,42 for rooms KB IGD, and 77,64 for the room IGD each of which fall into the average category. And for stress in work shows the number 113,38 that can be categorized in average. Based on theses results, it can be concluded that the workload of mental, physical, and work stress is have no significant effect to the nurses during activity, but it should be noted to avoid increasement on those variables.Keywords: workload of mental, workload of physical, work stress